Advances in protein-amino acid nutrition of poultry - Baker, David H (Amino acids, 2009)
The ideal protein concept has allowed progress in defining requirements as well as the limiting order of amino acids in corn, soybean meal, and a corn-soybean meal mixture for growth of young chicks. Recent evidence suggests that glycine (or serine) is a key limiting amino acid in reduced protein [23% crude protein (CP) reduced to 16% CP] corn-soybean meal diets for broiler chicks. Research with sulfur amino acids has revealed that small excesses of cysteine are growth depressing in chicks fed methionine-deficient diets. Moreover, high ratios of cysteine:methionine impair utilization of the hydroxy analog of methionine, but not of methionine itself. A high level of dietary l-cysteine (2.5% or higher) is lethal for young chicks, but a similar level of dl-methionine, l-cystine or N-acetyl-l-cysteine causes no mortality. A supplemental dietary level of 3.0% l-cysteine (7x requirement) causes acute metabolic acidosis that is characterized by a striking increase in plasma sulfate and decrease in plasma bicarbonate. S-Methylmethionine, an analog of S-adenosylmethionine, has been shown to have choline-sparing activity, but it only spares methionine when diets are deficient in choline and(or) betaine. Creatine, or its precursor guanidinoacetic acid, can spare dietary arginine in chicks.